Biomass decreases with species and functional group richness in natural phytoplankton assemblages - Παπανικολοπούλου, Λυδία-Άλκυστις (2014)
Ecosystem functioning and its linkage to biodiversity are central in current ecological research. Of the many ecosystem functions, primary productivity and the accumulation of biomass are most frequently investigated due to their high ecological and economic significance. Previous experimental evidence from artificial phytoplankton assemblages suggest that increasing species and functional group richness results in decreasing biomass in contrast to evidence from terrestrial plants. However, it is important to verify the validity of this finding using experimental conditions that are more realistic of processes occurring in the natural environment, such as: (a) a temporally variable, recurrent resource supply, (b) phytoplankton species that co-occur in the field and (b) species that can coexist at steady-state after a long self-organization process under the same environmental conditions. We hypothesize that when species can naturally coexist under a temporally variable, recurrent resource supply, they will demonstrate temporal complementarity in resource use which in turn may result in greater biomass yield compared to monocultures. An experimental design was employed testing the effect of increasing species and functional group richness on the resulting biomass. The 5 species originated from a species-rich field assemblage that was self-organized in semi-continuous cultures under constant environmental conditions for a period of 3 months. Overall, the results of the study are in agreement with previous experimental findings showing underyielding of species’ mixtures compared to monocultures. However this result seems to depend on the type of biomass measure used, as Chla demonstrated a unimodal trend with increasing richness.